Kompetensi Guru Dalam Mendidik Murid di Indonesia (Tinjauan Normatif Berbasis Paradigma Ulama Timur Sebagai Pendekatan) - Asiah, Siti; Resky, Muhammad; Pratama, Yosse Amanda (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The quality of education in Indonesia is one of the most important factors in achieving the goal of quality education. Various methods are applied if without competent and professional teachers, it is impossible for educational goals to be achieved. The purpose of this study is to explore the views of Eastern scholars, such as Imam an-Nawawi and al-Ghazâlî, on the traits and competencies that must be possessed by a teacher in educating students. The method in this research uses the literature study method, which begins with data collection, recording, and classification based on relevance. Then, the descriptive analysis approach is used to find facts and results of ideas, which are then generalised in the form of descriptions. After that, the researcher draws conclusions to prove the issues discussed. The results showed that based on the synthesis of the thoughts of Imam Ghazali, Imam Nawawi and Imam Amin Kurdi related to teacher competence, namely the pedagogical aspect, which includes mastery of material, understanding of students, curriculum development, and learning assessment. Personality aspects, which include a mature, wise, wise, patient, sincere, and authoritative personality. Professional aspects, which include mastery of various sciences related to the field of study they teach. Social aspects, which include the ability to communicate, work together, and build relationships.